2017
DOI: 10.2217/fon-2017-0115
|View full text |Cite
|
Sign up to set email alerts
|

PD-1/PD-L1 biology and immunotherapy in HPV-positive oral cancers

Abstract: Keywords• HPV • immune check points • immunotherapy • oral cancers • PD/PDL-1 HPV-infection related oral cancers are on the rise [2]. Conventional therapies (surgery, radiation and prophylactic vaccines) and some proposed nonconventional therapies (natural and synthetic antioxidants)-based treatments have limitations. In the light of recent advancement of immune checkpoints and their inhibitor molecule related cancer immunotherapies, we present updated information on the current status of PD-1/PD-L1 therapies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Their coexpression was analogous to the prognosis of different malignant tumors such as melanoma and OSCC. 8 9 Presently, two drugs are used to target PD-1. They are nivolumab and pembrolizumab.…”
Section: Drugs Targeting the Programmed Cell Death Receptormentioning
confidence: 99%
“…Their coexpression was analogous to the prognosis of different malignant tumors such as melanoma and OSCC. 8 9 Presently, two drugs are used to target PD-1. They are nivolumab and pembrolizumab.…”
Section: Drugs Targeting the Programmed Cell Death Receptormentioning
confidence: 99%
“…The top heading, bench and the invert arch excavation phase. In better underground conditions the excavation works were divided in top heading and bench phases only [3]. The Main Design defined rock categories, predicting the round lengths and defining support elements (system) for each of the rock category respectively (Table 1).…”
Section: Tunnel Excavation and Support Elements (Main Design Of The Project)mentioning
confidence: 99%
“…
BackgroundB7-H1 (also known as programmed death ligand or PDL-1) is an inhibitory molecule of T cells implicated in the protection of tumor cells from immune targeting [1,2]. Recent evidence has suggested some proportion of squamous cell carcinomas of the head and neck (SCCHN) expressed B7-H1, which has also been reported in breast, cervical, esophageal and colorectal cancers [3,4]. B7/PDL-1 binds the cognate receptor programmed death (PD-1) on cytotoxic T-cells, which leads to apoptosis and thus protection from lysis by activated T-cell (CTL) surveillance [5,6].Although several studies have reported screening for B7-H1 or PDL-1 among clinical patient samples, few if any have evaluated whether this expression is found among well-characterized oral cancer cell lines [7,8].
…”
mentioning
confidence: 99%